A replication of four quasi-experiments and three facts from 'The effect of file sharing on record sales: an empirical analysis' (Journal of Political Economy, 2007) - Stan J. Liebowitz (Kiel Institute for the World Economy (IfW), 2016)
The influential piracy paper by Professors Oberholzer-Gee and Strumpf, although mainly based on proprietary data, contained an 'important complement' to the main results, consisting of four "quasi-experiments" using publicly available data. This replication examines all of these quasi-experiments, first, by narrowly using identical data and statistical methods, as well as in a broader sense by extending or augmenting the data or methods. This study concludes that none of the four quasi-experiments provide evidence in support of OS' hypothesis that file-sharing has not harmed record sales.
Keywords: Z1; O3; L8; 330; Piracy; File Sharing; Oberholzer-Gee; Strumpf; Sound Recordings; Music; iTunes; Napster